Potensi Cengkeh (Syzigium Aromaticum) sebagai Antibakteri Methicillin Resistant Staphylococcus Aureus (MRSA) - Panggih Daru Panuluh (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
The threat of disease from bacterial strains that are pathogenic and resistant to antibiotics has increased in recent years. One of the bacteria that has experienced resistance is Staphyloccoccus aureus. Methicillin-Resistant Staphylococcus aureus (MRSA) is a strain of Staphylococcus aureus bacteria that resistants to the antibiotic methicillin. At present, vancomycin as the antibiotic of choice for the treatment of MRSA infections is reported to have decreased effectiveness. Many attempts have been made to develop alternative antibiotics. Clove (Syzygium aromaticum) is one of the native plants of Indonesia which has many benefits, including antibacterial. Eugenol, tannins, saponins, flavonoids, and alkaloids are the active components contained in cloves in inhibiting Methicillin-Resistant Staphylococcus aureus (MRSA) in vitro.